2021
DOI: 10.3390/polym13193333
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterned Polymer Molds Using Anodized Aluminum Templates for Anti-Reflective Coatings

Abstract: This work introduces a facile geometry-controlled method for the fabrication of embossed and engraved polymeric moth-eye-inspired nanostructures in imprinting molds using anodic aluminum oxide (AAO) templates, resulting in a novel anti-reflective transparent coating. The moth-eye nanostructures are prepared directly on the surface of a flexible polyethylene terephthalate (PET) substrate. As a prerequisite procedure, a UV-curable polyurethane acrylate resin is spun on the PET. The shape of the moth-eye nanostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Several groups, including our group, have already reported the fabrication of antireflection structures consisting of tapered nanopillar arrays by nanoimprinting using anodic porous alumina molds. [15][16][17][18][19]24,25) However, the polymers used in conventional nanoimprinting have poor heat resistance, and under conditions exceeding 100 °C, shape deformation and carbonization occur, making it difficult to use them in antireflection structures under high-temperature conditions. The tapered nanopillar arrays prepared in this study showed no significant change in shape or color even after heat treatment at 200 °C.…”
mentioning
confidence: 99%
“…Several groups, including our group, have already reported the fabrication of antireflection structures consisting of tapered nanopillar arrays by nanoimprinting using anodic porous alumina molds. [15][16][17][18][19]24,25) However, the polymers used in conventional nanoimprinting have poor heat resistance, and under conditions exceeding 100 °C, shape deformation and carbonization occur, making it difficult to use them in antireflection structures under high-temperature conditions. The tapered nanopillar arrays prepared in this study showed no significant change in shape or color even after heat treatment at 200 °C.…”
mentioning
confidence: 99%